Regulation of PKC-θ function by phosphorylation in T cell receptor signaling - Wang, Xiaohong; Chuang, Huai-Chia; Li, Ju-Pi; Tan, Tse-Hua (Frontiers in Immunology, 2012)
Protein kinase C (PKC)-θ is a serine/threonine kinase belonging to the calcium-independent novel PKC subfamily; its expression is restricted to certain tissues and cell types, including T cells. The signals delivered from T-cell receptor (TCR) and CD28 costimulatory molecules trigger PKC-θ catalytic activation and membrane translocation to the immunological synapse, leading to activation of NF-κB, AP-1, and NF-AT. These transcription factors are important for T-cell survival, activation, and differentiation. Phosphorylation of PKC-θ at multiple Ser/Thr/Tyr residues is induced in T cells during TCR signaling. Some phosphorylation sites play critical roles in the regulation of PKC-θ function and downstream signaling. The regulation mechanisms for PKC-θ phosphorylation sites are now being revealed. In this review, we discuss the current understanding of the regulation of PKC-θ function by phosphorylation during TCR signaling.